Experimental modeling for optimal accelerated curing of some Epoxy-Anhydride based filled resin systems - Qiang, Wei (2008)
The increasing application of thermosetting resins such as epoxy systems in the microelectronics and aerospace industries has highlighted the critical importance of the need to achieve an optimal curing process to maximize the performance of the resins, by understanding the cure mechanism and modeling the cure kinetics of the curing system. This project therefore has focused on the study of the cure kinetics of a neat and also filled epoxy-anhydride thermosetting resin. In particular, the gelation behavior of the system was characterized by means of a rheological approach.